The research, communication and education challenges for Lima’s museums in the context of Covid-19. A discussion of the challenges for the future based on their current situation and the experiences of the MALI and MUCEN - Delgado Pacheco, Sissy (2020)
Approximately 90% of the sixty thousand museums that exist around the world have closed either totally or partially due to Covid-19. In this new era, one of the main challenges that museums face is staying connected with their public. This study seeks to identify evidence of how prepared Lima’s museums are to face new challenges like that presented by Covid-19, and what recommendations they should follow in terms of research, communication and education. Following an exploratory discourse analysis based study, a list of recommendations was compiled and grouped into three categories: management of virtual collections, virtual visits, and the use of social networks as learning spaces. This research shows that those museums which implement strategies related to their research, communication and educational functions, as well as the use of information and communication technologies, will be in a position to face this new era with greater alternatives for the distribution of content to their public. In this new era, museums are accessible from anywhere in the whole world, and they must now adapt to a new role as living entities connected to and engaged with their digital community. The most significant challenges will be making their digital collections available online and bridging existing gaps in terms of educational initiatives. Finally, this research identifies five obstacles to implementation of the aforementioned recommendations: lack of market research, lack of financial sustainability, minimal inclusion strategies, the need for new training of museum staff, and the absence of collaboration among institutions.